Utilisateurs et non-utilisateurs des centres d’aide en français du postsecondaire au Québec : une étude comparative par la méthode d’appariement cas-témoin - Cabot, Isabelle (Canadian Journal of Higher Education, 2022)
Given the lack of formal information that helps to identify the effectiveness of post-secondary academic support centres, questions have been raised about what distinguishes students who use those services from those who do not. In order to examine the potential effectiveness of these success support structures, a comparative exploration of users and non-users of French language help centres (FHCs) was conducted at four higher education institutions. The case-control matching method was applied in order to optimize control for six confounding variables, determined by linear regression analysis. Thus, com-parative analyses were conducted using paired group t-tests. The variables compared were motivation to use CFO services, fear of negative judgement, and performance in French classes. The main results indicate that expectations of interest in the activities determine students’ tendencies to request them. Among users, the usefulness attributed to the services received was lower than what they initially expected. Nevertheless, at the end of the semester, their performance in French courses was higher than that of their non-user peers. These results are discussed in terms of the need to make the effectiveness of help centres more explicit to students, and lead to practical recommendations for doing so. Further studies should explore the effectiveness of various post-secondary academic help centres (disciplinary or multidisciplinary) in Canada in order to maximize their potential for positive impact on academic success.